Analysis of the Suitability of the Capacity and Quality of the Jakarta Government in Implementing SNI 03-1733-2004 and the Long Term Regional Development Plan for Jakarta 2005 – 2025 - Santoso, Nur Iman; Barus, Lita Sari (UI Scholars Hub, 2024)
center for government, economy, and politics. The ethnic diversity influences the community's access to political facilities such as government offices, polling stations, and information centers. Aims: The research aims to analyze the enhancement of government capacity. It is necessary to develop the professionalism of government officials and institutions to achieve good governance in the implementation of Indonesian National Standard (SNI) 03-1733-2004. Methods: Literature and demographic studies were conducted to implement SNI 03-1733-2004. Results: Out of 44 sub-districts, only 15 meet the SNI, and out of 267 urban villages, only 125 comply with the standard. This indicates a need for improvements in public facilities and services. Conclusion: Addressing the challenges of accessibility, security, and community participation is key to creating a democratic and inclusive political environment. Collaboration between the government, community, and stakeholders is required to support political activities beneficial to all Jakarta residents.